Students' Mathematical Problem-Solving Processes Across Self-Efficacy Levels in High School - Jasmine Kaylla Gemilang; Krisna Satrio Perbowo (JURNAL PENDIDIKAN MATEMATIKA, 2026)
Mathematical problem-solving ability is an essential competency influenced by cognitive and affective factors, including self-efficacy. This study aims to analyze the characteristics of high school students' mathematical problem-solving ability across high, moderate, and low levels of self-efficacy. The research method used was a mixed-methods approach with a sequential explanatory design involving 108 eleventh-grade students at a high school in Indonesia. The research instruments included a self-efficacy questionnaire and a mathematical problem-solving test on SLETV material developed based on Polya's indicators. The results indicate a gradation of abilities aligned with self-efficacy levels. Students in the high category were able to systematically and flexibly manage all stages of Polya's model. Students in the moderate category began to encounter obstacles in completing algebraic manipulations, while those in the low category faced fundamental challenges from the modeling stage onward. A key finding revealed a common pattern across all levels: low metacognitive awareness regarding the "review" indicator. The conclusion of this study emphasizes the importance of synergy between strengthening psychological aspects and fostering the habit of self-evaluation in mathematics learning. Keywords: mathematical problem-solving, self-efficacy, polya stages